Features of cardiac remodeling and GDF 15 and NTproBNP levels in patients with heart failure and preserved ejection fraction depending on the history of myocardial infarction - Ya. V. Zemlianyi; N. A. Zemliana (Zaporožskij Medicinskij Žurnal)
Aim. To determine the relationships between serum concentrations of growth and differentiation factor 15 (GDF 15) and NTproBNP and features of heart remodeling in patients with heart failure and preserved ejection fraction (HFPEF) depending on the history of Q-myocardial infarction (MI).